An Alberta Approach to School Improvement in an Australian Rural School - Shipway, Bradley; Chaseling, Marilyn Joan (Alberta Journal of Educational Research, 2021)
This article reports on the experiences of teachers at a small rural school located in the North Coast region of New South Wales in Australia who participated in a school improvement project based on an approach developed over many years by David Townsend and Pam Adams in Alberta, Canada. The project involved monthly meetings between the teachers at the school, including the school’s Principal, and an external leadership team who facilitated the meetings employing the processes of collaborative inquiry and generative dialogue. All participants were volunteers in the North Coast Initiative for School Improvement. Over three years, the school achieved a significant improvement in its literacy and numeracy outcomes, thereby attracting acclaim from the Department of Education in New South Wales for the excellence of its achievements. The teachers at the school attributed this success to a school improvement model based on the Alberta approach, and transported to the Australian context known as the North Coast Initiative for School Improvement. The processes of collaborative inquiry and generative dialogue were said to have taught them ways to engage with evidence, to create professional space for deep and critical self-reflection, to improve their daily work efficiency, and to promote more student autonomy in learning. Keywords: school improvement, collaborative inquiry, generative dialogue, North Coast Initiative for School Improvement Cet article rapporte les expériences des enseignants d'une petite école rurale située dans la région de la côte nord de la Nouvelle-Galles du Sud en Australie qui ont participé à un projet d'amélioration de l'école basé sur une approche développée depuis de nombreuses années par David Townsend et Pam Adams en Alberta, Canada. Le projet prévoyait des réunions mensuelles entre les enseignants de l'école, y compris le directeur de l'école, et une équipe de direction externe qui facilitait les réunions en utilisant les processus d'enquête collaborative et de dialogue génératif. Tous les participants étaient des bénévoles de la North Coast Initiative for School Improvement. En trois ans, l'école a amélioré de manière significative ses résultats en matière de lecture, d'écriture et de calcul, s'attirant ainsi les éloges du ministère de l'Éducation de Nouvelle-Galles du Sud pour l'excellence de ses réalisations. Les enseignants de l'école ont attribué ce succès à un modèle d'amélioration de l'école basé sur l'approche albertaine et transposé au contexte australien, connu sous le nom de North Coast Initiative for School Improvement. Les processus d'enquête collaborative et de dialogue génératif leur ont appris à s'appuyer sur des preuves, à créer un espace professionnel pour une autoréflexion profonde et critique, à améliorer l'efficacité de leur travail quotidien et à promouvoir une plus grande autonomie des élèves dans leur apprentissage. Mots clés : amélioration des écoles, enquête collaborative, dialogue génératif, North Coast Initiative for School Improvement